2001
DOI: 10.1590/s0100-879x2001000700006
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability under resting conditions in postmenopausal and young women

Abstract: The aim of the present study was to compare the modulation of heart rate in a group of postmenopausal women to that of a group of young women under resting conditions on the basis of R-R interval variability. Ten healthy postmenopausal women (mean ± SD, 58.3 ± 6.8 years) and 10 healthy young women (mean ± SD, 21.6 ± 0.82 years) were submitted to a control resting electrocardiogram (ECG) in the supine and sitting positions over a period of 6 min. The ECG was obtained from a one-channel heart monitor at the CM5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
24

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
5
28
0
24
Order By: Relevance
“…Previous studies have also shown changes in the autonomic control of HR following natural (12)(13)(14)27) or surgical menopause (15). In agreement with the results of these studies, our results show that menopause can cause an imbalance of the autonomic nervous control of the cardiovascular system that shifts toward sympathetic hyperactivity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have also shown changes in the autonomic control of HR following natural (12)(13)(14)27) or surgical menopause (15). In agreement with the results of these studies, our results show that menopause can cause an imbalance of the autonomic nervous control of the cardiovascular system that shifts toward sympathetic hyperactivity.…”
Section: Resultssupporting
confidence: 92%
“…Autonomic modifications of cardiovascular control have also been observed in the aging process (11,12). In women, both aging and postmenopausal hormonal changes contribute to modifications of the autonomic control of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hautamäki et al (50), hot flashes and HRT were not related to the changes in HRV. The absence of clinically meaningful relationships between cardiovascular autonomic indices and vasomotor symptoms in menopause revealed in our study agree with some other results (5,10,11,44,50). It is evident that changes in levels of sex hormones in menopause are the main factor determining vasomotor symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…It has been found that autonomic dysfunction is an important factor for the evaluation of risk of cardiovascular events in CVD patients (2,3). Age-related changes in autonomic control of the cardiovascular system (CVS) are also well known (2,(4)(5)(6). The difference of heart rate variability (HRV) indices in pre-and postmenopausal women has been reported (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Our results that show a 1% increment of DHA and EPA as being associated with a decrease of 1.4 bpm and 2.6 bpm, respectively, among women are in line with a pooled estimate obtained in a meta-analysis that assessed the effect of using fish oil supplementation on HR (21). Differences in the impact of n-3 PUFAs between women and men could be due to varying levels of estrogen, since these hormones have been suggested to have a cardio-protective effect in young women as well as in postmenopausal women who are undergoing hormone replacement therapy (34)(35)(36). In this sample, 41 women (30%) were classified as being menopausal if they had not had a period in the last 12 months or if they had had a hysterectomy.…”
Section: Discussionsupporting
confidence: 81%